Gender, job engagement, and extra-role performance - Rio Novrizal Huda Pratama; Ana Mariana; Bram Hadianto (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2026)
This investigation examines the impact of work engagement and gender on extra-role performance, as well as the influence of gender on work engagement. Additionally, it examines the moderating effect of gender on the relationship between work engagement and extra-role performance. The study population consisted of 300 employees at a baby clothing manufacturing company in Bandung. Using Slovin's formula, a sample size of 291 individuals was determined. Moreover, they were taken using a simple random sampling technique. Unfortunately, after the survey, 258 responses were collected via an online questionnaire, yielding a response rate of 88.66%. Covariance-based structural equation modeling (SEM) with subgroup analysis was used to analyze the data. The analysis revealed that (1) higher employee engagement leads to better extra-role performance, (2) male employees exhibit higher engagement than female employees, (3) the extra-role performance between males and females is the same, and (4) gender does not moderate the relationship between work engagement and extra-role performance. Based on these findings, company owners should address employee concerns and announce initiatives during formal meetings to express appreciation for increased work engagement, thereby fostering extra-role performance